Pemanfaatan Bahan Alam dalam Mengembangkan Kreativitas Seni Anak Usia Dini Di TK Al-Muna Kabupaten Bireuen - Safura, Amuna; Rizkia, Zita; Salpina; Maisura; Junaidi Putri, Dwi Adhinda (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This research aims to determine the use of natural materials to develop artistic creativity in early childhood at Al-Muna Kindergarten. Natural materials are often found in the surrounding environment so they can develop artistic creativity in young children. Artistic creativity can easily be increased in children by utilizing natural materials found in the child's surroundings. The research method used is descriptive qualitative. Data collection techniques use observation and interview techniques. The subjects of this research were group A teachers and children from Al-muna Kindergarten consisting of 12 children in group A of Al-muna Kindergarten, namely 8 boys and 4 girls. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The research results show that using natural materials is very good for developing children's creativity, because they are easy to find in the surrounding environment and children can be creative with natural materials in their environment.